Ferrocenyl imidazolo[2, 1-b]-1, 3, 4-thiadiazoles: A microwave-assisted catalyst-free synthesis, characterization, and biological activities. Issue 5 (May 2021) - Liu, Yuting; Yang, Lan; Yin, Dawei
Ferrocenyl imidazolo[2, 1- b ]-1, 3, 4-thiadiazoles are synthesized using 2-amino-5-substituted-1, 3, 4-thiadiazole and α-bromoacetyl ferrocene as substrates under microwave-assisted and catalyst-free conditions. The structures are characterized by infrared, 1H nuclear magnetic resonance, 13C nuclear magnetic resonance, mass spectrometry, and elemental analysis. Compared with conventional methods, the present protocol has the advantages of being rapid, efficient, environmentally friendly, and low cost. The results of biological activity studies showed that the products displayed better activities than those of 2-amino-5-substituted-1, 3, 4-thiadiazole. The biological activities of compounds in which R = phenyl were better than those with alkyl groups. Compounds with electron-withdrawing groups on the aryl moiety showed increased biological activities.